THE DIGESTIVE TRACT DEVELOPMENT OF THE TIGER GROUPER Epinephelus fuscoguttatus LARVAE TREATED WITH THYROXINE HORMONE - Ahmad Muzaki; Ketut Mahardika; Indah Mastuti; Wawan Andriyanto; Yasmina Nirmala Asih; Ida Komang Wardana (Indonesian Aquaculture Journal, 2012)
Thyroxin administration in tiger grouper larval rearing was conducted to determine its effect on development of digestive tract of the larvae. Newly hatched larvae were treated with 0 mg/L (control), 0.1 mg/L, and 0.2 mg/L of thyroxin for 2 hours in a 30 L tank before were transferred into a 1 m3 rearing tank. Samples were collected daily until 10 DAH and every 3 days until 40 DAH. Development of digestive tract was observed using histological method. For all treatments, the digestive tract was the same on 1 DAH and 2 DAH. The digestive tract of 1 DAH larvae was still closed and still in the form of a simple tube. The mouth, buccopharynx, liver, pancreas, and rectum were found on 2 DAH. On 3 DAH, the esophagus, stomach, intestines, and anus started to develop. At this stage, the digestive tract of larvae treated with and without thyroxin started to become distinguishable. Several goblet cells were noticed in the rectum of the treated larvae but not in the control. Digestive tract developed earlier in treated larvae compared to the control group, such as appearance of tongue, gill raker, fundic, and cardiac stomach development, formation of pharyngeal tooth, and gastric gland. Metamorphosis of larvae into juvenile on treated larvae occurred than that the control larvae earlier.